Feasibility Of Ceramic Ultra- And Nanofiltration Membranes For Removal Of Endotoxins - Czermak, Peter; Ebrahimi, Mehrdad; Hackel, Rene; Catapano, Gerardo (Filtech Exhibitions Germany, 2008)
The removal of endotoxins, a potential contaminant of dialysis water and dialysate, is a very difficult task. The endotoxin removal capacity of commercial ceramic membranes with a nominal molecular weight cut-off of < 1,000 and adsorber membranes was investigated. The dead-end filtration results showed that all investigated ceramic membranes produce water meeting the European standards when challenged with low endotoxin concentrations, but only one membrane type succeeded at high endotoxin concentrations. In addition, we present preliminary analysis of the factors determining bacterial fragment removal from water of different ceramic and polymeric adsorptive membranes.
Keywords: Ceramic membrane; Charged membrane; Retention efficiencies; Dialysis; Water treatment